Acetylation of interferon regulatory factor‐5 suppresses androgen receptor and downregulates expression of Sox2. (29th March 2021) - Acidereli, Hilal; Turut, Fatma Aysun; Cevik, Ozge
Abstract : Interferon regulatory factor‐5 (IRF5) is a transcription factor and has essential cellular mechanisms as a tumour suppressor gene. IRF5 protein function is irregular in various human cancers, and its role in prostate cancer is also unknown. This study presents the first evidence that IRF5 expression is controlled with androgen receptor (AR) signalling interaction and stem cell factors (Nanog, Oct4, Sox2) in prostate cancer. Human prostate cancer cell lines (PC3, DU145 and LNCaP) were transfected plasmids and assessed for cellular localization of IRF5 and AR interaction with IF‐staining. Co‐immunoprecipitation and ChIP assay were used to detect the IRF5 and AR protein‐protein interaction and IRF5 stem cell factors protein‐gene interaction. The target relation between IRF5, AR, CREB, p300, ISRE, ARE and NF‐кB was tested by luciferase assay. IRF5 was low expressed in androgen‐dependent prostate cancer cells and tissues. The analysis of human prostate cancer clinical samples supports the interaction of IRF5 and AR in a pathological role, as IRF5 expression is down‐regulated in the tumours' advanced stages. Tumour suppression mechanism of IRF5 and SOX2 levels in cells reduces and causes AR acetylation. Those affect the prostate cancer mechanism by modifying the cellular response in the signal pathway. IRF5 can be promising for treating androgen‐dependent prostate cancers and is a therapeutic protein for new drug studies.